Culture technique of endangered Notopterus chitala (Hamilton, 1822) with Oreochromis niloticus for domestication in pond habitat (Bangladesh Journal of Scientific and Industrial Research, 2017)
An experiment was carried out for a period of 180 days (1stApril to 30 th September) in 2015 to find out a the suitable culture technique of Notopterus chitala (Hamilton-Buchanan, 1882) in pond habitats located at the Hatchery Complex, Department of Fisheries, University of Rajshahi. The experiment was conducted under 3 treatments (T1: only feed used, T2: feed and Tilapia, T3: only Tilapia used) each with 3 replications. Mean stocking weight of Notopterus chitala was 21.4±0.27 g for all treatments. Basal fertilization was same for all the treatments (cowdung: 1235 kg/ha, urea: 50 kg/ha, TSP: 50 kg/ha). Feed (8-10% of body weight) and fertilized (weekly with cowdung 1000 kg/ha,) based farming was followed in all treatments. Mean value of water temperature varied from 32.53±0.04°C (T2) to 32.57±0.03°C (T1) to transparency 32.34±0.68 (T2) cm to 33.87±0.37cm (T3), Dissolved Oxygen 4.76±0.04mg/l (T3) to 4.91±0.04 mg/1 (T1), pH 7.62±0.03 (T1) to 7.70±0.05 (T2) , alkalinity 127.04±1.4 mg/l (T2) to 131.46±0.92 mg/1 (T3),respectively. The mean value of different growth parameters varied with the followings-final weight 380±.88 g (T1) to  645 ± .57g (T2), weight gain 358.6 ± .14g (T1) to 623.60± .02g (T2), SGR (% bwd-1) 3.84±.02 (T1) to 4.54± .01(T2).The survival rate between 93.33±6.67 % (T1) to 100 ± 0.00 %(T2), and the total production of Notopterus chitala was found 1593.2±2.46(T2) Kg/ha/180 days which was significantly higher than that of others treatments 938.6 ±31.29 (T1), 1133.7±62.98  (T3) respectively. The growth parameters are significantly different among the treatments. The total production of Tilapia was observed 1790.18±0.7(T2) kg/ha/180 days which was higher than 1584.9±0.39(T3).The combined production (Chital + Tilapia) of fish was obtained 3383.2±2.86(T2) which was higher than those of 938.6 ±31.29(T1) and 2718.6±50.1(T3) respectively.The total income raised from 394200±6.36BDT/ha (T1) to 736548±24.04 BDT/ha (T2), net profit 209180±12.49BDT/ha (T1) to 468258±17.63BDT/ha (T2) and CBR 1.13±.01 (T1) to 1.75±.02 (T2) respectively and all growth parameters were significantly (P